Development of human mast cells from umbilical cord blood cells by recombinant human and murine c-kit ligand. - Mitsui, H (1993)
Both human and mouse c-kit ligand induced differentiation of human mast cells in a long-term culture of the mononuclear cells of umbilical cord blood. Growth factor activity for human mast cells present in conditioned medium of BALB/3T3 fibroblasts was due to mouse c-kit ligand. Recombinant c-kit ligand induced differentiation and proliferation of mast cell progenitors in early stages of culture. However, apparent selective growth of mast cells by c-kit ligand in cord blood cell cultures is mainly due to the effect of the cytokine to selectively maintain survival of immature mast cells. Electron microscopic analysis indicated that human mast cells developed by c-kit ligand were similar to human mast cells in the lung and gut mucosa, while those developed in coculture of cord blood cells with Swiss albino/3T3 fibroblasts were similar to skin mast cells. This conclusion was supported by the fact that the majority of mast cells developed by c-kit ligand contained only tryptase in their granules, whereas those developed in the cocultures contained both tryptase and chymase. It was also found that mast cells developed by c-kit ligand were immature even after culture for 14 weeks. Nevertheless, these cells express Fc epsilon RI, and could be sensitized with human IgE for anti-IgE-induced release of histamine, prostaglandin D2, and leukotriene C4.